PENGARUH POJOK BACA TERHADAP PENINGKATAN MINAT BACA SISWA KELAS V DI SDS BHAKTI LUHUR - Lita Kusuma Astuti; Sholehuddin Sholehuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Reading interest in Indonesia is very low compared to other countries, hence the introduction of the reading corner as an effort to improve reading skills. This study aims to determine the effect of the reading corner on students' interest in reading. This research is a quantitative research with survey method. The population in this study were 22 fifth grade students of Bhakti Luhur Elementary School. The sampling technique used saturated sampling. Data collection techniques were carried out with a questionnaire as the main source, while observation and documentation studies as supporting sources. The test in this study used validity and reliability tests, and the T test. The results of this study indicate that there is an influence of the reading corner on increasing interest in reading. Based on the hypostatistical test calculated by the t test, the results obtained if the significant value of 0.000 is less than 0.05 with a confidence level of 95%, then the conclusion is H0 is rejected and H1 is accepted. This means that there are differences between male and female students. Male students are more interested in reading books in the reading corner than female students. The results of this study are useful for teachers in mobilizing students to read diligently.